Fixed target matrix for femtosecond time-resolved and in situ serial micro-crystallography - C. Mueller (Structural Dynamics, 2015)
We present a crystallography chip enabling in situ room temperature crystallography at microfocus synchrotron beamlines and X-ray free-electron laser (X-FEL) sources. Compared to other in situ approaches, we observe extremely low background and high diffraction data quality. The chip design is robust and allows fast and efficient loading of thousands of small crystals. The ability to load a large number of protein crystals, at room temperature and with high efficiency, into prescribed positions enables high throughput automated serial crystallography with microfocus synchrotron beamlines. In addition, we demonstrate the application of this chip for femtosecond time-resolved serial crystallography at the Linac Coherent Light Source (LCLS, Menlo Park, California, USA). The chip concept enables multiple images to be acquired from each crystal, allowing differential detection of changes in diffraction intensities in order to obtain high signal-to-noise and fully exploit the time resolution capabilities of XFELs.